Reduction of Matrix Metallopeptidase 13 and Promotion of Chondrogenesis by Zeel T in Primary Human Osteoarthritic Chondrocytes - Sanchez, Christelle; Hemmer, Kathrin; Krömmelbein, Natascha; Seilheimer, Bernd; Dubuc, Jean-Emile; Antoine, Christophe; Henrotin, Yves (Frontiers in Pharmacology, 2021)
Objectives: Zeel T (Ze14) is a multicomponent medicinal product. Initial preclinical data suggested a preventive effect on cartilage degradation. Clinical observational studies demonstrated that Ze14 reduced symptoms of osteoarthritis (OA), including stiffness and pain. This study aimed to explore these effects further to better understand the mode of action of Ze14 on human OA chondrocytes in vitro. Methods: Primary chondrocytes were obtained from the knees of 19 OA patients and cultured either as monolayers or in alginate beads. The cultures were treated with 20% or 10% (v/v) Ze14 or placebo. For RNA-seq, reads were generated with Illumina NextSeq5000 sequencer and aligned to the human reference genome (UCSC hg19). Differential expression analysis between Ze14 and placebo was performed in R using the DESeq2 package. Protein quantification by ELISA was performed on selected genes from the culture medium and/or the cellular fractions of primary human OA chondrocyte cultures. Results: In monolayer cultures, Ze14 20% (v/v) significantly modified the expression of 13 genes in OA chondrocytes by at least 10% with an adjusted p-value < 0.05: EGR1, FOS, NR4A1, DUSP1, ZFP36, ZFP36L1, NFKBIZ, and CCN1 were upregulated and ATF7IP, TXNIP, DEPP1, CLEC3A, and MMP13 were downregulated after 24 h Ze14 treatment. Ze14 significantly increased (mean 2.3-fold after 24 h, p = 0.0444 and 72 h, p = 0.0239) the CCN1 protein production in human OA chondrocytes. After 72 h, Ze14 significantly increased type II collagen pro-peptide production by mean 27% (p = 0.0147). For both time points CCN1 production by OA chondrocytes was correlated with aggrecan (r = 0.66, p = 0.0004) and type II collagen pro-peptide (r = 0.64, p = 0.0008) production. In alginate beads cultures, pro-MMP-13 was decreased by Ze14 from day 7–14 (from −16 to −25%, p < 0.05) and from day 17–21 (−22%, p = 0.0331) in comparison to controls. Conclusion: Ze14 significantly modified the expression of DUSP1, DEPP1, ZFP36/ZFP36L1, and CLEC3A, which may reduce MMP13 expression and activation. Protein analysis confirmed that Ze14 significantly reduced the production of pro-MMP-13. As MMP-13 is involved in type II collagen degradation, Ze14 may limit cartilage degradation. Ze14 also promoted extracellular matrix formation arguably through CCN1 production, a growth factor well correlated with type II collagen and aggrecan production.